Uma proposta para o ensino progressivo da relatividade restrita no nível médio - Oliveira, Antônio Nunes de (2013)
Several studies in the area of physics teaching, as well as official documents, indicate a need to introduce concepts related to Modern and Contemporary Physics at the secondary school. In this paper we present a new proposal for the teaching of Relativity at the average level of education, where the contents are divided in blocks and spread over the three years. The aim of this paper is threefold: (i) verify through research with students that they feel the need to acquire knowledge of Relativity, (ii) teachers agree with the inclusion of relativity in high school and with the fact that this must be made from the first series of EM, (iii) produce educational material to propose a division of the contents of Relativity to the three years and can be used by teachers. To do this follow the constructivist teaching method, arrange the contents to cover the three years and prepare educational material aimed at meaningful learning theory of David Ausubel and conceptual maps of Joseph D. Novak. The result of applying the material shows that Relativity is able to arouse students' interest in physics and the lessons that both students and teachers yearn for a sequenced approach, which takes place over the three years.